A Fatal Case of Subcapsular Liver Hemorrhage in Late Pregnancy: A Review of Hemorrhages Caused by Hepatocellular Hyperplastic Nodules. (17th August 2012) - Yajima, Daisuke; Kondo, Fukuo; Nakatani, Yukio; Saitoh, Hisako; Hayakawa, Mutsumi; Sato, Yayoi; Otsuka, Katsura; Sato, Kaoru; Iwase, Hirotaro
Abstract: A previously healthy 23‐year‐old woman was admitted to hospital with abdominal pain at 39 weeks 0 days of pregnancy. The patient suffered sudden cardiopulmonary arrest during the observation and unfortunately died. An autopsy was performed to determine the cause of death. Opening of the peritoneal cavity revealed 2220 mL of blood and a subcapsular hematoma weighing 1060 g on the anterior surface of the right hepatic lobe. A lesion of c . 1 cm in diameter was noted at the center of the front surface of the right hepatic lobe, which was shown on histological examination to be a focal nodular hyperplasia‐like lesion. The cause of death was found to be hypovolemic shock caused by bleeding of the rupture of the hepatocellular hyperplastic nodule. Although some previous case reports describe hemorrhage from such lesions, forensic pathologists should be aware that they can lead to severe bleeding and sometimes death.